The COVID-19 Pandemic and Outbreak Inequality: Mainstream Reporting of Singapore's Migrant Workers in the Margins - Kaur-Gill, Satveer (Frontiers in Communication, 2020)
Singapore saw a majority of COVID-19 infections plaguing low-skilled migrant construction workers by late April 2020. In the initial phases of the outbreak, mainstream frames were quick to highlight the gathering of low-skilled workers in open areas as sites to be surveilled, shaping the divisive practices of othering in early frames on migrant worker behaviors. These reports were manufactured as Singaporeans continued to gather in public spaces in large groups during the outbreak. Mainstream reports were quick to inform audiences of the surveillance and control for disciplining migrant workers. As the crisis developed to impact migrant workers predominantly, the erasures are recovered with mainstream press reporting worker vulnerabilities and discussing the structural implications of managing migrant labor as neoliberal subjects. The structural conditions of migrant labor were, in fact, centered in mainstream narratives, and dormitories as public health threats were extensively discussed, shedding light on discourses relating to outbreak inequality. The rights framework, however, remained largely absent in mainstream news frames about migrant workers